PENERAPAN METODE K- MEANS CLUSTERING DALAM PENGELOMPOKAN PENERIMA BANTUAN SOSISAL PADA DESA WEEKOMBAK BERBASIS WEB - Marinus Tanggu; Trisno; Diana Reby Sabawaly (Indonesian Journal of Engineering and Computer Science (IJEC), 2025)
Social assistance is a form of government intervention aimed at reducing the economic burden on the poor. However, in its implementation, many problems remain, such as inaccurate targeting of recipients due to invalid or poorly structured data. This results in unfair distribution of aid and has the potential to trigger social conflict in the community. Web-based systems also facilitate real-time data management and access. With a web-based system integrated with the K-Means algorithm, the process of identifying eligible community groups for social assistance can be carried out objectively and transparently The development of this application will significantly assist village officials and social institutions in making accurate, data-driven decisions. Therefore, this study aims to develop and implement a web-based information system that can group social assistance recipients in villages using the K-Means Clustering method. Based on the results of research and data analysis conducted in Weekombaka Village in Southwest Sumba, it can be concluded that the number of clusters generated is not significantly different and is even nearly the same.